Flashcard Media Innovation in Thematic Science Lessons Growth and Development of Living Creatures in Elementary Schools - Annissa Syafarina Sari; Krisna Wijaya; Ridho Gata Wijaya (MIMBAR PGSD Undiksha, 2023)
The difficulty of the material presented in science subjects and the teacher's lack of ability to utilize learning media have an impact on students' low ability to understand learning material. So, the aim of this research is to develop flashcard media on the growth and development of creatures in elementary schools so that students can more easily understand the material being taught. The research design used is research and development (R&D) which goes through 7 stages of development design according to Borg & Gall. The data collection techniques used in this research were interviews, observation and questionnaires. The data analysis technique uses quantitative descriptive. The results of this research and development show that the flashcard learning media regarding the growth and development of living things to equip students' speaking skills is declared suitable for use. This can be seen from the results of material validation with an average score of 4.8 which is in the "very good" category and media validation with an average score of 3.95 in the "good" category. Apart from that, the results of student responses in the initial field trial got an average score of 4.6 which was included in the "very good" category and the results of teacher responses got an average score of 4.7 which was included in the "very good" category as well as the results of student responses in the main field trial got an average score of 4.49 which is in the "very good" category. With this, it can be concluded that this flashcard learning media is suitable for use in the learning process in class III of elementary school.